Diversity Insects of Spring in Mutis Timau Nature Reserve, TTS District, NTT Province - Chatarina Gradict Semiun; Gaudensius U. U. Boli Duhan (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
Insect diversity is believed to be used as a bio-indicator of spring quality, this study aimed at determining the spring insect diversity around the Mutis Timau Nature Reserve. The study was conducted from June to August 2019. Insects were caught by using the yellow pan trap and hand sorting. The diversity of spring insects was determined based on the Shannon-Wiener diversity index (H'), species richness index (R1), species dominance index (D), and evenness index (E). The results showed that 16 species belong to 11 families, and five orders of insects. The families included Gryllidae, Gryllotalpidae, Tetrigidae, Formicidae, Pompilidae, Apidae, Ochteridae, Veliidae, Hydrometridae, Nepidae, Coenagrionidae, Libellulidae, Carabidae, and Coccinellidae. The Shannon-Wiener species diversity index and the wealth index of the species of springs were classified as moderate (H '= 2.12 and R1 = 4.19). There was no type of spring insects dominated (D = 0.23). All springs insects were found to have almost the same level of evenness (E<1), with a value of 0.76. Abiotic factors such as pH and soil temperature were within the tolerance range of spring insects.ÃÂ ÃÂ